Sociology as a Theoretical Science (Based on Nikolay KareyevвЂ™s Manuscript вЂњGeneral Methodology of the HumanitiesвЂќ) - Alexey V. Malinov; Evgeniya A. Dolgova (Социологический журнал, 2020)
This article sets the task of actualizing a fragment of the unpublished work “General methodology of the Humanities” by Nikolay Kareyev (1850–1931). Kareyev’s role in the history of Russian sociology is unique in that he was not only working to popularize the new science of society, but he was also its first historian. The history of Russian sociology for Kareyev, in fact, coincided with some facts from his own biography: Kareyev knew the first Russian sociologists and was one of the founders of a new scientific discipline. In the work “General methodology of the Humanities”, written at the time of reading his educational course at Petrograd University, Nikolay Kareyev summed up his methodological thoughts, paying particular attention to sociology. He considered it a discipline that synthesizes the achievements of the social sciences. By his reasoning, these social sciences were political economics, law and politics (state studies). The view of sociology as an integrating or synthesizing discipline granted it a methodological function. According to Kareyev, the sociological method is in fact a “higher synthesis” or eclectic method. Due to censorship restrictions, the manuscript of the “General methodology of the Humanities” was not published in the 1920’s. Its typescript is stored in the manuscript research department of the Russian state library. As of today the text of the manuscript has only partially been published. The research article is accompanied by the publication of an excerpt from the chapter six “Theoretical Humanities”, dedicated to the synthesizing methodology of sociology.